(NpEDAGOG)QÆKA (B:s)E (NNAW^(B. (NPOS)QÆBNIK (B/s)E - (NqGUPOW(B, (NwASILX wASILXOWI^(B,s; (NgOLOWKO(B, (Ns(B. (Nw(B.,s; (NnI^KALO(B, (Nn(B. (Ng(B.,s; (NgON^ARENKO(B, (Ns(B. (Nu(B.s; (NwASQNOWI^(B, (Ng(B. (Np(B.s ((NkI)QÇW (B:s)E (NlIB)QÆDX(B,s)E, 2003)
(Nu NAW^ALXNOMU POS)QÆBNIKU WIKLADENO TEORETIKO(B-(NMETODOLOGÆ^NÆ OSNOWI PEDAGOGÆKI(B, (NKL@^OWÆ PROBLEMI DIDAKTIKI Æ TEORÆÇ WIHOWANNQs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpEDAGOG)QÆKAs)E; (NWIHOWANNQs; (NDIDAKTIKAs; (NNAW^ALXNIJ PROCESs; )QÆ(NDEAL WIHOWANNQs)E; (NFORMUWANNQ OSOBISTOST)QÆs)E; (NPEDAGOG)QÆ^NE DOSLÆDVENNQs)E; (NPEDAGOG)QÆ^NIJ PROCESs)E; (ND)QÆAGNOSTIKA NAW^ANNQs)E; (NMETODI WIHOWANNQs; (NPRINCIPI WIHOWANNQs; (NSOC)QÆALXNE SEREDOWI]Es)E; (NSAMOWIHOWANNQs